Persepsi dan Preferensi Konsumen terhadap Penggunaan Material Bangunan Berbasis Limbah - Frisgian Dewantara; Rijaluddin Rijaluddin; Firda Rasyidian Andayani; Lily Tambunan; Dewi Larasati (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Environmental challenges stemming from the escalating volume of waste necessitate innovative solutions, one of which involves utilizing waste as a raw material for building materials. However, prevailing research in this domain has predominantly concentrated on their characteristics/performances, with a notable dearth in discussions pertaining to consumer-centric aspects. The objective of this research is to examine public responses, comprehension levels, and considerations associated with the utilization of waste-derived materials. Therefore, the development of waste-derived materials can be facilitated towards mass production. Employing qualitative research methods, this research unveils misconceptions surrounding waste-derived materials, as well as the readiness and the consideration aspects, such as material characteristic/performance, sustainability, economic factors, aesthetics, functionality, availability, and knowledge. The findings are anticipated to contribute insights for decision-making processes, policy formulation, and industrial practices, fostering the informed integration of waste-derived materials in the construction and related sectors.